Physiological and biochemical responses of Carthamus tinctorius L. under salt stress - Somayeh Vaghari; Arash Fazeli; Reza Haghi; Fariba Shohani (Kuwait Journal of Science)
Salinity stress is one of the important abiotic factors that affect the physiological and metabolic activities of plants. The present research was conducted in a factorial experiment based on a completely randomized design in the research greenhouse of Ilam University during the agricultural year 1403–1402. In this study, salinity stress at two levels (control and 120 mM) was applied to four genotypes (Cart193, Cart158, Cart83, and Cart223) to evaluate growth indices, photosynthesis rate, relative water content (RWC), soluble carbohydrate content (TSC), proline (Pro), and enzymatic and non-enzymatic antioxidants in Carthamus tinctorius L. The mean comparison results showed that under 120 mM salinity stress, the aerial parts had a reduction of 6.2 % in plant height and 23.07 % in the number of seeds per head, respectively, in the genotypes Cart83 and Cart158 compared to the control. Additionally, the number of seeds per head, 25 % seed weight, 24.39 % total seed yield, 18.86 % biological yield, 19.89 % harvest index, 0.78 % head diameter, 1.82 % photosynthesis rate 60 %, and RWC 31.74 % showed the highest reduction in the genotype Cart223 compared to the control. Furthermore, the content of 25.71 % Pro, 29.45 % TSC, 42.38 % anthocyanins, and 31.22 % phenols showed the highest increase in the genotype Cart193 compared to the control. However, among the enzymatic antioxidants, only guaiacol peroxidase (GPX) showed the highest increase of 55.05 % in the genotype Cart223 compared to the control. The results of this study indicate that compatible osmolytes and non-enzymatic antioxidants act as effective markers for understanding the defense mechanisms of Carthamus tinctorius under salinity stress conditions.